Implementation of Artificial Intelligence in Political Advertising in Indonesia - Khairunnisa, Putri; Mulyadi, Mulyadi (Universitas Syiah Kuala, 2024)
A recent technological advancement that helps meet many of the demands of people in many spheres of life is artificial intelligence. Politics has a role in one of these elements. As an example, artificial intelligence (AI) has started to be used in this context, particularly in Indonesian political campaigns. In more detail, the problems with AI's application in politics pertain to the efficiency, dangers, and obstacles that the field's future technological advancements will have to overcome in order to contribute to a positive transformation of political advertising. The study's findings indicate that there are a number of risks associated with using artificial intelligence (AI) technology for political marketing in the form of political advertising, but there are also advantages for the future growth of political advertising media. Cooperation and community socialization are necessary for the effective and efficient use of AI in politics, including in Indonesia.